Spiritual Intelligence as a Moderator in the Influence of Work Loyalty, Individual Characteristics, and External Motivation on Employee Performance - Ariasanti, Yossi; Nuraini, Betti; Rimbano, Dheo; Paleni, Herman (Universitas Bangka Belitung, 2025)
This research addresses the gap in public sector employee performance models in Indonesia, which are still dominated by structural factors such as incentives, while the integration of values (psychological and spiritual) is rarely tested quantitatively. This research examines the influence of work loyalty, individual characteristics, and external motivation on employee performance, as well as the role of spiritual intelligence as a moderator at the Lubuklinggau City Agriculture Office. A quantitative survey method was used on 81 employees; data was collected through questionnaires, observations, and document reviews, then analyzed using simple linear regression, t-tests, correlation tests, and Moderated Regression Analysis (MRA). The results show that all three variables have a positive and significant effect on performance, and spiritual intelligence strengthens the relationship between each variable and performance. The findings emphasize the urgency of a value-based performance framework that integrates spiritual dimensions into bureaucratic performance management practices. Limitations include a single-agency design, potentially biased self-assessment, and narrow scope. Nevertheless, this study contributes empirical evidence of the moderating effect of spiritual intelligence and offers a value-based performance framework that integrates psychological and spiritual parameters in the context of government organization.